EMPOWERING YOUNG LEARNERS: FOSTERING OWNERSHIP AND CONTRIBUTION IN EARLY CHILDHOOD PROJECT-BASED LEARNING - Sudaryanto, Memet; Amelia, Dinda; Ulya, Chafit (Jurnal Penelitian Kebijakan Pendidikan, 2025)
This study investigates student engagement and contributions in project-based learning within early childhood education settings. The objectives of this approach include developing skills, emotions, traits, and critical thinking abilities. The participants were teachers and students from eight ECE institutions in Tegal and Pekalongan districts. Data were drawn from principals’ and teachers’ observations of classroom learning, with an activity checklist serving as the primary instrument. Data analysis followed four steps: collection, reduction, conclusion drawing, and presentation. Findings indicate that students engaged in projectbased learning were able to practice problem-solving skills, while teachers served as project planners and facilitators to maximize learning outcomes. The achievement graph of project learning success shows that each topic has accomplished its goal. The Trash Can Project (Topic 3) achieved a 100% success rate, while the Bread-Making Project (Topic 6) reached 98%. These results strengthened students’ understanding of communication processes and fostered pride in project outcomes. The study highlights the importance of policies that encourage schools to adopt child-centered learning models. The success of projectbased learning also depends on careful planning, appropriate scheduling, developmental readiness, and teachers’ classroom management experience.